Vanadium disulfide flakes with nanolayered titanium disulfide coating as cathode materials in lithium-ion batteries - Lu Li (Nature Portfolio, 2019)
VS2 is a promising cathode material for lithium-ion batteries, but is susceptible to Peierls distortion during (de)lithiation. Here the authors show that VS2 cathodes can be stabilized by conformally coating them with a nanoscale TiS2 protective layer, leading to impressive electrochemical performance.